STUDY OF THE EFFECT OF MAGNETIC FIELDS ON ELECTROENCEPHALOGRAPHY MEASUREMENT IN FARADAY’S CAGE - Galih Restu Fardian Suwandi; Siti Nurul Khotimah; Freddy Haryanto; Suprijadi Suprijadi (Program Studi Fisika Universitas Negeri Jakarta, 2021)
Electroencephalography (EEG) is a method for recording the brain's electrical activity through electrodes placed on the scalp's surface. The amplitude of the EEG signal is in the 40–100 V range, with the five main frequencies in the 0 to 100 Hz range. The EEG is non-stationary and very susceptible to various disturbances, especially frequency disturbances, so eliminating troubles in the raw EEG data is essential to obtain helpful information reflecting brain activity. Interference in the EEG signal comes from muscles, eye movement and blinking, power lines, and interference with other devices. The distractions overlap. Shielding is required to perform an EEG without the risk of interference and ambient background noise. This study tested how the influence of magnetic field disturbances on EEG measurements was carried out in the Faraday cage and an unprotected room. The magnetic field was measured before, during, and after the EEG was operated. EEG measurements were performed on subjects who were conditioned to rest for 5 minutes. The EEG signals generated when EEG recordings were performed in the Faraday and the unprotected rooms were compared. It was found that the difference in the value of the magnetic field originating from electronic devices around the subject does not significantly affect the EEG measurement results.